2004
DOI: 10.5326/0400261
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Clomipramine Trial for the Treatment of Feather Picking Disorder in Cockatoos

Abstract: This double-blind, placebo-controlled trial was performed to evaluate the efficacy of clomipramine for the treatment of feather picking disorder in otherwise healthy cockatoos. Twenty cockatoos with chronic feather picking disorder were screened for medical conditions and then randomly assigned to either a clomipramine or placebo group. Based on caregiver assessments and physical examination findings, treatment with clomipramine significantly improved feather picking when compared to a placebo at 3 weeks (P=0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 20 publications
0
11
0
5
Order By: Relevance
“…In animal models such as acral-lick dermatitis in canines, compulsive behaviors are reduced with SRIs8, 65. Response to SRIs has also been reported for avian psychogenic feather plucking66, 67. Similarly, SRIs often reduce compulsive cleaning and washing behaviors in OCD and compulsive skin picking and grooming behaviors in BDD55.…”
Section: Neurobiology Of Pathological Groomingmentioning
confidence: 96%
“…In animal models such as acral-lick dermatitis in canines, compulsive behaviors are reduced with SRIs8, 65. Response to SRIs has also been reported for avian psychogenic feather plucking66, 67. Similarly, SRIs often reduce compulsive cleaning and washing behaviors in OCD and compulsive skin picking and grooming behaviors in BDD55.…”
Section: Neurobiology Of Pathological Groomingmentioning
confidence: 96%
“…Similarly, large age ranges were reported for initiation of feather picking among cockatoos in another study. 25 However, in African grey parrots, 7 of 8 cases with known ages of onset initiated feather picking at less than 1 year of age. Recognition of the wide range of ages at which feather picking began, including very young birds, should encourage practitioners to ask owners about early behavioral history and to explore a range of potential behavioral diagnoses.…”
Section: Bird Characteristicsmentioning
confidence: 99%
“…Preening refers to a movement with the bill intended to care for the duck's plumage aimed toward the breast, shoulders, wings, or back feather (Lersel and Bol, 1958). Injurious feather picking has been described and refers to an auto-mutilation behavior as opposed to feather pecking that occurs between birds, particularly in galliforms (Madsen, 1966;Grindlinger and Ramsay, 1991;Bordnick et al, 1994;Jenkins, 2001;Seibert et al, 2004). It has been suggested that the incidence of these injurious behaviors may be related to a birds' ability to forage in their bedding substrate (Rodenburg et al, 2004(Rodenburg et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%